Alcohol and tobacco consumption affects bacterial richness in oral cavity mucosa biofilms - Thomas, Andrew Maltez; Gleber-Netto, Frederico Omar; Fernandes, Gustavo Ribeiro; Amorim, Maria; Barbosa, Luisa Fernanda; Francisco, Ana Luisa Noronha; Guerra de Andrade, Arthur; Setubal, João Carlos; Kowalski, Luiz Paulo; Nunes, Diana Noronha; Dias-Neto, Emmanuel (BMC microbiology, 2014)
Background Today there are more than 2 billion alcohol users and about 1.3 billion tobacco users worldwide. The chronic and heavy use of these two substances is at the heart of numerous diseases and may wreak havoc on the human oral microbiome. This study delves into the changes that alcohol and tobacco may cause on biofilms of the human oral microbiome. To do so, we used swabs to sample the oral biofilm of 22 subjects; including 9 control-individuals with no or very low consumption of alcohol and no consumption of tobacco, 7 who were chronic and heavy users of both substances and 6 active smokers that reported no significant alcohol consumption. DNA was extracted from swabs and the V1 region of the 16S rRNA gene was PCR amplified and sequenced using the Ion Torrent PGM platform, generating 3.7 million high quality reads. DNA sequences were clustered and OTUs were assigned using the ARB SILVA database and Qiime . Results We found no differences in species diversity and evenness among the groups. However, we found a significant decrease in species richness in only smokers and in smokers/drinkers when compared to controls. We found that Neisseria abundance was significantly decreased in both groups when compared to controls. Smokers had significant increases in Prevotella and Capnocytophaga and reductions in Granulicatella , Staphylococcus, Peptostreptococcus and Gemella when compared to the two other groups. Controls showed higher abundance of Aggregibacter , whilst smokers/drinkers had lower abundances of Fusobacteria . Samples from only smokers clustered closer together than to controls and smokers/drinkers, and also had a significant reduction in inter-group dissimilarity distances, indicating a more homogenous group than controls. Conclusions Our results indicate that the continued use of tobacco or alcohol plus tobacco significantly reduces bacterial richness, which apparently leads to a reduction in inter-group variability, turning the respective biofilms into a more homogenous microenvironment in terms of bacterial community composition, with possible consequences for human oral diseases.